An Investigation into the Suitability of Ordering D-dimers for Patients with Suspected DVT in the A&E at Waterford Hospital - Tobin, Oliver (Trinity Student Medical Journal, 2003)
Objective: The objectives of this study were to assess the suitability of ordering D-dimer assays and to investigate the need for a validated risk assessment model in the evaluation of patients with a clinical suspicion of deep venous thrombosis in patients attending the Accident and Emergency unit of Waterford Regional Hospital. Methods and Patients: Admission cards of 106 consecutive patients ,for whom D-dimer assays were ordered, were evaluated according to the Wells Criteria to determine whether the patients had a high, medium or low probability risk of having a deep venous thrombosis. (DVT) This information was correlated with initial clinical impression, presenting complaint, the result of the D-dimer test and the results of ultrasonography, if performed. Results: There were 30 positive D-dimer results returned from the 106 analysed. Of those, 19 (63.3%) had a Wells score suggesting low probability of DVT, 10 (33.3%) had a medium probability, and 1 (3%) had a high probability of DVT. For the remaining 76 negative D- dimer results, 59 (77.6%) had a low probability Wells score, 14 (18.4%) were in the medium probability group and 3 (3.9%) were in the high probability group. This study proposes that the introduction of a clinically validated model for the diagnosis of DVT/pulmonary embolism (PE) would rationalise the ordering of D-dimers and make the diagnosis of DVT/PE more evidenced based.